2011
DOI: 10.1021/cm103595x
|View full text |Cite
|
Sign up to set email alerts
|

Instability of the Lithium Garnet Li7La3Sn2O12: Li+/H+ Exchange and Structural Study

Abstract: We demonstrate for the first time the instability of the lithium garnet Li 7 La 3 Sn 2 O 12 toward moisture. In ambient air a spontaneous Li þ /H þ exchange occurs leading to Li 7-x H x La 3 Sn 2 O 12 . The lithium released is combined with the atmospheric CO 2 under the Li 2 CO 3 form making Li 7 La 3 Sn 2 O 12 a CO 2 absorbent. The structural study of the exchanged Li 7-x H x La 3 Sn 2 O 12 phase has been performed on samples obtained by heating at reflux the mother compound in a solution of benzoic acid/ et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
123
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(136 citation statements)
references
References 22 publications
10
123
2
Order By: Relevance
“…It was demonstrated that the instability of Li 7 La 3 Zr 2 O 12 (Al) in water led to the decrease of ionic conductivity of ceramic bulk samples [18]. The spontaneous ionexchange phenomenon in the ambient air was also observed in tetragonal Li 7 La 3 Sn 2 O 12 [19]. Similar proton ion-exchange phenomena also occurred in other solid electrolytes such as Li 0.30 La 0.57 TiO 3 with perovskite structure [20].…”
Section: Introductionmentioning
confidence: 69%
“…It was demonstrated that the instability of Li 7 La 3 Zr 2 O 12 (Al) in water led to the decrease of ionic conductivity of ceramic bulk samples [18]. The spontaneous ionexchange phenomenon in the ambient air was also observed in tetragonal Li 7 La 3 Sn 2 O 12 [19]. Similar proton ion-exchange phenomena also occurred in other solid electrolytes such as Li 0.30 La 0.57 TiO 3 with perovskite structure [20].…”
Section: Introductionmentioning
confidence: 69%
“…27 One, however, needs to be very careful in the selection of elements, since a substitution on the octahedral Li-site will result in a blocking of the diffusion pathways. Nevertheless, considering the known structural instability of these compounds to humidity and air, which lowers the ionic conductivity significantly, [74][75][76] it seems difficult to obtain the necessary ionic conductivity using the current approaches. However, there is a wide variety of promising materials systems such as glassy materials, glass ceramics, Li rich anti-perovskites and sulfide superionic conductors (e.g.…”
Section: Dalton Transactions Perspectivementioning
confidence: 99%
“…However, the impedance profiles did reveal a change after immersion in these solutions, as shown in Fig. 4 [39]. An increase of grain boundary resistance was also observed for Li 1 3 , which has high lithium-ion conductivity and is stable in saturated LiOH with saturated LiCl, is thus a promising candidate for the protective layer of a water-stable lithium electrode.…”
Section: Nasicon-type Lithium-ion Conducting Solid Electrolytementioning
confidence: 84%